ON LAPLACE TRANSFORMS OF GENERALIZED WHITTAKER FUNCTION OF MULTI-VARIABLES \(M_λ,μ1···μk(x_1, ..., x_k)\) - Kamarujjama, M.; Khan, Waseem A. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, a Laplace transform of generalized Whittaker function is derived which is used to obtain further some partly bilateral and partly unilateral generating function and series expansion. Some special cases are also discussed.